Pengaruh Daya Tarik Iklan dan Potongan Harga Terhadap Keputusan Pembelian di Shopee pada Mahasiswa Prodi Manajemen Universitas Islam Malang Angkatan 2020 - Aziz, Achmad Ridwan Abdul; Priyono, Achmad Agus; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Shopee has a promotional strategy by placing advertisements in various online media and providing lots of promotional discounts on various products. The aim of this research is to analyze the partial and simultaneous influence of advertising attractiveness and price discounts on purchasing decisions among Management Study Program students who use Shopee at the Islamic University of Malang. The research method used was a quantitative survey. Sampling used a non-probability sampling method with a purposive sampling technique of 82 respondents. Data were analyzed using multiple linear regression analysis. The results of this research show that simultaneously the attractiveness of advertising and price discounts have a significant effect on purchasing decisions among Management study program students at the Islamic University of Malang, class of 2020. Partially, the attractiveness of advertising has a significant effect on purchasing decisions for Management study program students at the Islamic University of Malang, Class of 2020. Partially. Price discounts have a significant influence on the purchasing decisions of Management study program students at the Islamic University of Malang class of 2020. Keywords: Purchase Decisions, Advertising Attractiveness, Price Discounts, Shopee